IHMIS- JA KÄYTTÄYTYMISTIETEET SOTATIETEELLISESSÄ TARKASTELUSSA - Huhtinen, Aki-Mauri; Mäkinen, Juha; Tallberg, Teemu (Tiede ja ase, 2015)
Abstract Throughout the 20-year history of the National Defence University, leadership and military pedagogy have consolidated their position as both academic subjects and military science research fields. At the beginning of 2014, the University’s Department of Leadership and Military Pedagogy acquired a tenured professorship, which added a new military science research discipline to the ranks – military sociology. Clearly, the basic research foundations for human and behavioural science are now in place. In addition, the Department’s resources are supplemented by a joint professorship specializing in the biology of physical activity at Jyväskylä University, creating a fruitful interdisciplinary research climate. In collaboration with the Riihimäki-based Finnish Defence Research Agency’s Behavioural Science Department, these leadership, pedagogy, sociology, and sport science disciplines provide the basis for continued multidisciplinary research into aspects of human and behavioural science that have a bearing on defence. In this article, professors from the Department of Leadership and Military Pedagogy reflect on trends in these research fields and express their views on the way in which the academic programme is organized. The main message is that the stage is now set for basic academic research. Doctoral programmes in military sciences are being developed and collaboration with the Finnish Defence Research Agency is set to begin. Added to this, each scientific field – leadership, military pedagogy and military sociology – has connections to a network of civilian researchers.